Response to: 'Anakinra for palmoplantar pustulosis: results from a randomized, double‐blind, multicentre, two‐staged, adaptive placebo‐controlled trial (APRICOT)': reply from the authors. (2nd March 2022) - Cro, S.; Smith, C.H
Abstract : We believe that there is significant interest in the role of IL‐1 in the pathomechanism of palmoplantar pustulosis. However, the APRICOT study failed to demonstrate a therapeutic effect of the IL‐1 receptor antagonist. So, we recommend that the authors perform an additional subgroup analysis based on the presence or absence of plaque psoriasis.